Peningkatan kemampuan Pedagogical Content Knowledge (PCK) guru mata pelajaran rumpun MIPA di Kabupaten Kepulauan Selayar - Fajar Arwadi; Muharram Muharram; Suwardi Annas; Ahmad Fudhail Majid (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of this program is to improve thePedagogical Content Knowledge (PCK) capabilities.Specifically, PCK includes teacher knowledge about thematerial taught, pedagogical knowledge, and knowledge ofstudents related to the material. This program was carried outin Selayar Islands Regency, Benteng City. There were about40 participants of mathematics and natural science teacherswho involved in this program. This implementation consists ofseveral activities, namely the conducting of PCK material bythe speakers, workshop/training to improve PCK capabilities,and PCK ability tests. The result of this program is that theknowledge of the pedagogical content of the trainingparticipants' teachers has increased.